2017
DOI: 10.1038/srep45090
|View full text |Cite
|
Sign up to set email alerts
|

B lymphocytes play a limited role in clearance of Campylobacter jejuni from the chicken intestinal tract

Abstract: Campylobacter jejuni is the leading cause of foodborne bacterial gastroenteritis with contaminated poultry meat its main source. Control of C. jejuni is a priority for the poultry industry but no vaccines are available and their development hampered by poor understanding of the immunobiology of C. jejuni infection. Here we show the functional role of B lymphocytes in response to C. jejuni in the chicken through depletion of the B lymphocyte population (bursectomy) followed by challenge. B lymphocyte depletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
(34 reference statements)
1
26
0
2
Order By: Relevance
“…It varied from no impact on the Campylobacter cecal load to significant decreases of up to 4.2 log 10 CFU/g of cecal content. Taking all these results together, this means that additional mechanisms to antibodies may be involved in protection against Campylobacter , as it was recently suggested [ 32 ].…”
Section: Discussionmentioning
confidence: 55%
“…It varied from no impact on the Campylobacter cecal load to significant decreases of up to 4.2 log 10 CFU/g of cecal content. Taking all these results together, this means that additional mechanisms to antibodies may be involved in protection against Campylobacter , as it was recently suggested [ 32 ].…”
Section: Discussionmentioning
confidence: 55%
“…However, it has proven to be a formidable challenge to eliminate this natural commensal from its host during the period prior to slaughter, when the organism is immunologically silent (76). We have demonstrated that the E. coli-based C. jejuni N-glycan vaccine is equally effective in broiler chickens, reducing C. jejuni colonization to undetectable levels in most birds.…”
Section: Discussionmentioning
confidence: 79%
“…These results provide circumstantial evidence that C. jejuni -infection may be controlled by humoral immunity as suggested before [ 14 ]. In Cyclophosphamide-immunocompromised birds the same trend was observed that antibodies may play a significant role in the bacterial clearance phase later after inoculation [ 16 ]. Further studies need to be done, to evaluate the local C. jejuni -specific IgA-response to confirm the role of local humoral immunity in C. jejuni -colonization.…”
Section: Discussionmentioning
confidence: 79%
“…However, the role of humoral immunity in Campylobacter control has been discussed controversially [ 15 ]. Recent studies with chemically B cell-compromised chickens indicated that humoral immunity may be important in the clearance of C. jejuni from the small intestine [ 16 ].…”
Section: Introductionmentioning
confidence: 99%